Paket Kebijakan Ekonomi untuk Mengerakan UKM di Tingkat Desa - Ahok Alpa Beta (Universitas Muhammadiyah Jambi, 2016)
The government has announced tujuanya Economic Policy Package is to facilitate the business sector in obtaining capital loans and expedite matters pembankkan issuance of land certificates. This is the strategy most perfect economic policy today. All policies certainly have weaknesses and strengths of each. The benefits of these regulations can be viewed from two sides, from the government side as regulators and from the community or in this case SMEs. For the government, which has disbursed KUR loan through Community or SMEs provide protection to the wider community through processes that are easy and quick. SMEs should provide social and economic benefits after the receiving credit business loans or called KUR. Once a policy or regulation is not in line with expectations, the policy must be evaluated for their evaluation will be obtained feedback related to policy mismatch with the expected performance results. Thus, the evaluation helps policy makers at the stage of assessment of policies against the policy making process. Evaluation policy does not only produce conclusions about how far the problem has been resolved, but give input on the clarification and critique of the values ​​underlying the policy, assist in the adjustment and re-formulation of the problem.